Ecotourism Conservation Potential Of Proboscis Monkey (Nasalis Larvatus) At Samunsam Wildlife Sanctuary, Sarawak, Malaysia - Mohamad Abid, Kamaruzzaman; Muhammad Ismeer, Ismail; Roberta Chaya, Tawie Tingga (Faculty of Forestry, Universiti Putra Malaysia, 2017)
The Proboscis monkey (Nasalis larvatus) is estimated to be approximately 160 individuals left in Samunsam Wildlife Sanctuary (SWS) and 1000 individuals left in Sarawak. The population of proboscis monkey is decreasing since this species is fragile to habitat loss and habitat destruction that live within only 10% of the total protected areas (TPA’s) gazetted in Sarawak. A river boat survey conducted in 2014-2015 showed an average of 0.305 groups/km surveyed. The abundance recorded is much higher than the two previous studies conducted in 2001 and 2004. Unfortunately, the construction of the Sarawak Pan Borneo Highway from Sematan to Kg. Telok Melano that crossed over the Samunsam River gives a big impact on the abundance and survival of proboscis monkey in the future. Thus, the study proposed that conservation efforts on proboscis monkey can be increased through ecotourism activities. Through highly potential ecotourism activities, it can help to trigger conservation awareness to the public and also bring economic benefits to the local communities.